2021
DOI: 10.1186/s40337-021-00478-6
|View full text |Cite
|
Sign up to set email alerts
|

Managing the premenstrual body: a body mapping study of women’s negotiation of premenstrual food cravings and exercise

Abstract: Background Women’s eating behaviours and exercise patterns have been found to fluctuate across the menstrual cycle, manifested by premenstrual food cravings and reduced exercise. However, the meaning and consequences of premenstrual changes in eating and exercise behaviours remains underexplored. The aim of this qualitative study was to explore how women who feel negatively about their premenstrual bodies construct and experience premenstrual changes to eating and exercise practices, which disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Additionally, both the sex and the underlying knowledge appeared to influence any support provided as has been previously demonstrated (Brown & Knight, 2022;Clarke et al, 2021) and which is further expanded upon in theme 3. This is an important challenge for practitioners to consider, given changes to nutritional intake mediated by cravings and external pressures can have implications on females' mental health and feelings of self, which may be tied to overall body dissatisfaction (Ryan et al, 2021).…”
Section: Theme 2: Sport Nutrition Practice Is Influenced By a Range O...mentioning
confidence: 99%
“…Additionally, both the sex and the underlying knowledge appeared to influence any support provided as has been previously demonstrated (Brown & Knight, 2022;Clarke et al, 2021) and which is further expanded upon in theme 3. This is an important challenge for practitioners to consider, given changes to nutritional intake mediated by cravings and external pressures can have implications on females' mental health and feelings of self, which may be tied to overall body dissatisfaction (Ryan et al, 2021).…”
Section: Theme 2: Sport Nutrition Practice Is Influenced By a Range O...mentioning
confidence: 99%
“…The majority of these cases was thus found, regardless of gender, in the anaerobic and combat sports that have weight categories. It can be suggested that the relatively higher use by women may be related to the greater variations in body weight because of the fluctuations in hormonal status during the menstrual cycle (Ryan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both, Microsoft Word and NVIVO12 software [ 24 ] were used for coding. A table was constructed, which entailed the overall themes and subthemes together with corresponding data [ 19 ] (see also additional file 3 and 4 for verbatims), which was discussed and adapted during regular online meetings. These meetings also served to discuss the overall progress, difficulties arising during the coding process as well as the meaning and implication of findings.…”
Section: Methodsmentioning
confidence: 99%